Search for supersymmetry with jets, missing transverse momentum and at least one hadronically decaying tau lepton in proton-proton collisions at root s=7 TeV with the ATLAS detector ATLAS Collaboration - Onofre, A. (2012)
A search for production of supersymmetric particles in final states containing jets, missing transverse momentum, and at least one hadronically decaying τ lepton is presented. The data were recorded by the ATLAS experiment in View the MathML sources=7 TeV proton–proton collisions at the Large Hadron Collider. No excess above the Standard Model background expectation was observed in View the MathML source2.05fb−1 of data. The results are interpreted in the context of gauge mediated supersymmetry breaking models with Mmess=250 TeVMmess=250 TeV, N5=3N5=3, μ>0μ>0, and Cgrav=1Cgrav=1. The production of supersymmetric particles is excluded at 95% C.L. up to a supersymmetry breaking scale Λ=30 TeVΛ=30 TeV, independent of tan β , and up to Λ=43 TeVΛ=43 TeV for large tan β.